Determinants of the Saving Behaviour of Saudi Households: An Investigation of Saving Motives and Awareness - Sarea, Suaad Yahya; Badkook, Roaa Osama (Journal of Economic, Administrative and Legal Sciences, 2022)
This paper aims to investigate the effect of saving motives and awareness on the saving behaviours of Saudi Arabian households. To this end, we collected primary data through a survey of 432 Saudi households. This study considered seven categories of saving motives (emergencies, retirement, children, necessities, home, holidays, and investment) and two measures of saving awareness (concept and importance). The results showed that emergencies, necessities, retirement, and investment were the most potent motives for demonstrating saving behaviours. In addition, there was also evidence that the saving awareness of Saudi households also positively influences their saving behaviours. The findings may inform policy makers and behavioural finance specialists in developing products and services to encourage household saving behaviours and improve saving awareness through financial education.